QUANTITATIVE ANALYSIS OF BANDED STRUCTURES IN DUAL-PHASE STEELS - Krebs, Benoit; Hazotte, Alain; Germain, Lionel; Gouné, Mohamed (Image Analysis and Stereology, 2011)
Dual-Phase (DP) steels are composed of martensite islands dispersed in a ductile ferrite matrix, which provides a good balance between strength and ductility. Current processing conditions (continuous casting followed by hot and cold rolling) generate 'banded structures' i.e., irregular, parallel and alternating bands of ferrite and martensite, which are detrimental to mechanical properties and especially for in-use properties. We present an original and simple method to quantify the intensity and wavelength of these bands. This method, based on the analysis of covariance function of binary images, is firstly tested on model images. It is compared with ASTM E-1268 standard and appears to be more robust. Then it is applied on real DP steel microstructures and proves to be sufficiently sensitive to discriminate samples resulting from different thermo-mechanical routes.